Klasifikasi Data Penduduk Penerima Bantuan Pangan Non Tunai Menggunakan Algoritma Naïve Bayes - Satrianansyah; Armanto; Susanto (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Indonesia's population is increasing, and people are starting to move from one island to another. This is caused by people who certainly want to get a more decent life. Every citizen makes various efforts to fulfill their standard of living by working as farmers, entrepreneurs, private employees and other jobs. But sometimes the jobs that have been done are not also able to raise the standard of living and the economy of the population, so there are still many people who fall into the poor category. There are many government programs to help alleviate the economic level of the poor, one of which is Non-Cash Food Assistance (BPNT). However, there is an obstacle where there is a lack of socialization to the community regarding this matter because in some areas there is not a system that is sufficient to obtain precise and accurate information about the data collection of the poor. This also causes a lot of abuse of the right to get assistance from the government. Assistance that should be obtained by the poor but then does not fall into the right hands due to the many irresponsible people who take advantage of conditions like this. Research on data collection of poor people this time was conducted at the Tebing Tinggi City Social Service, where in this Social Service there is no application that can record poor people in the city accurately and accurately. In this research, the Naïve Bayes algorithm is used to determine which people are categorized as poor and deserve to receive assistance. The result of this research is a website system that can display the results of calculations of which people are eligible to receive and which are not eligible to receive assistance. The purpose of this research is to help the Tebing Tinggi City Social Service in terms of facilitating village assistance to classify potential recipients of non-cash assistance in the city of Tebing Tinggi. The results of the research obtained the results of the value of people who are eligible to receive assistance based on the data in the Inoutkan is 2.947808918805